AERC: Research and Practice - Alan B. Knox (Adult Education Research Conference, 2009)
I appreciate this opportunity to share a few reflections on adulteducation research fifty years ago and today. The first snapshot is the formation of AERC, and its relation to the field of practice in the 1950s. The second snapshot is future directions regarding relations between scholarship, professional practice, society, and the importance of leadership on behalf of scholarly practice to benefit adult learners and society.